Ingênuas almas: famílias negras, solidariedade e liberdade em Lages-SC (1871-1888) - Maurer, Jasmini Letícia (2021)
The present research recounts the experiences of black families from the perspective of the ingênuos who were born in Lages in the province of Santa Catarina from 1871 to 1888. In order to achieve that the study analyzed the documents archived by the Catholic Church (baptism, marriage and death certificates), Freedom Lawsuit records, post mortem inventories, newspapers of local and provincial circulation, the Census of 1872, reports of the Province President and the Law no. 2.040/1871. Basing the analysis on a qualitative and quantitative nominal crossing of sources it was possible to bring forward what was experienced by the black families in their enslaved and freed condition. Apported in Social History and Microhistory it was possible to inquire the aftermath of the legislation in Santa Catarina as well as to trace its impact on the children born under the aegis of the Free Birth Law while their relatives struggled on the fragile borders of slavery and freedom in the outlying city. Thus, it was possible to interpret the strategies of compadrio, the establishment of families and the paths the mothers of theses ingênuos traced towards their emancipation.